The relationship between patient, carer and staff perceptions of need in an assertive community treatment team in South Africa - Cossie, Qhama Zamani (Department of Psychiatry and Mental Health, 2016)
Background The assessment of a patient's individual needs offers many benefits and it is essential for planning and implementing services and interventions. Need is a subjective concept and may be defined from several perspectives. Patient, carer and staff interests may differ, influencing their perspectives in defining needs. Traditionally, the staff perspective on needs has taken priority but the steady growth of the 'user movement' and 'recovery philosophy' has led to this being challenged. This study aimed to establish patient, carer and staff perceptions of patient need, the extent to which these perceptions were homo- or heterogeneous, and what factors were associated with local perceived needs. Methods The study was informed by a systematic review of the literature focused on the individual needs of people with severe mental illness assessed from multiple perspectives. Patients, carers and staff on the Valkenberg Hospital assertive community treatment (ACT) service were assessed using the Camberwell Assessment of Need Short Appraisal Schedule to evaluate needs. Patient global functioning and current levels of psychopathological symptoms were assessed using the Global Assessment of Functioning scale and the Positive and Negative Syndrome Scale respectively. Kappa statistics were computed to assess agreement in the participants' perspectives.